A study of the incidence of Post-traumatic Stress Disorder (PTSD) among emergency relief workers in selected international organizations : prevailing conditions, policies and attitudes to stress-related illnesses in relief organizations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Philosophy in Development Studies at Massey University - Small, Alison Mary (Massey University, 2000)
The staff of United Nations and non-governmental organisations (NGOs) are frequently at the forefront of emergency relief efforts. Such staff, including consultants, often work long hours, are sent at short notice to assignments in the field and often constitute the frontline of assistance in relief work. In the process of providing help to the victims of emergencies, relief workers may themselves be affected by the stress resulting from working in highly emotionally and physically charged situations. Since 1980, Post-traumatic Stress Disorder was officially recognised as a disorder by the American Psychiatric Association which may affect those who have been exposed and or experienced repeated exposure to large-scale disasters and emergencies, in particular. Given the multiple stresses involved in providing emergency relief, it is possible that relief workers may be vulnerable to developing PTSD and or other severe stress-related conditions. This study seeks to determine, from among the staff of several UN agencies and NGOs active in this area, the incidence of PTSD. The study also considers how the attitudes, policies and conditions extant in these organisations may exacerbate or alleviate the development of PTSD and provides suggestions, through a review of literature on the subject, on measures which can be taken by these organisations to prevent, minimize or at the very least address the problem.
Keywords: Post-traumatic stress disorder; Emergency medical personnel; Disaster relief; Disasters; Psychology; Mental health services